Selenium Concentration and Speciation in Formulae for Infants: Implications for Infant Health - Małgorzata Dobrzyńska; Zofia Wojciechowska; Anna Szczepańska-Álvarez; Katarzyna A. Kaczmarek-Kryszak; Juliusz Przysławski; Przemysław Niedzielski; Sławomira Drzymała-Czyż (Foods, 2026)
Inappropriate concentrations of elements in formulae for infants may lead to adverse health effects. Selenium (Se) is a trace element essential for the proper development of infants. It is naturally present in human milk and is also added to infant formulae. However, both insufficient and excessive Se intake may be harmful. The aim of this study was to determine Se concentrations and chemical forms in 148 formulae for infants available on the Polish market and to assess their nutritional safety. Se concentrations were determined using inductively coupled plasma mass spectrometry (ICP-iCRC-MS). Se speciation was performed using a HPLC system coupled to ICP-iCRC-MS. The Se concentrations in most analyzed formulae were in good agreement with the recommended EU limits (median 4.5 µg/100 kcal, range 0–15.6 µg/100 kcal). However, the estimated daily intake for 6-month-old infants exceeded the tolerable upper intake level in six formulae, indicating a potential health risk. Speciation analysis showed that the dominant Se forms were sodium selenite and sodium selenate, and their levels were mostly consistent with the manufacturers’ declarations. Additionally, trace amounts of selenometionine (SeMet) and methyloselenocysteine (MeSeCys) were detected. Therefore, regular monitoring of the composition of infant formulae remains necessary. The detection of SeMet and MeSeCys provides new avenues for research on Se content and Se speciation in formulae intended for infants.